Left ventricular mass response to extra-corporeal life support (ECLS) in infants. (December 2017) - Files, Matthew D.; Portman, Michael A.; McMullan, David M.; Bhat, Aarti H.
Abstract: Background: The effect of extracorporeal life support (ECLS) on left ventricular mass in infants is unknown. We sought to explore the effect of ventricular loading conditions on left ventricular mass for infants supported with ECLS. Methods: Transthoracic echocardiograms (TTE) of infants placed on venovenous (VV) or venoarterial (VA) ECLS were reviewed. Left ventricular mass index (LVMI) was calculated on TTE performed prior to initiation of ECLS (baseline) and after decannulation (post-ECLS). Results: TTE from 31 infants (mean age 30 days, mean weight 3.6 kg) were analyzed (19 VA-ECLS, 12 VV-ECLS). Patients received ECLS for 2–29 days (mean 8 days). Baseline LVMI was 47 g/m 2.7 in the VA-ECLS group and increased by 156% after separation from ECLS ( p  = 0.007). LVMI was 64 g/m 2.7 in the VV-ECLS group and increased by 143% of baseline ( p  = 0.009). Younger children showed a more significant increase in LVMI ( p  = 0.002) while mode, indication, and duration of ECLS did not separately influence LVMI increase. Increased mass occurred in patients with sub-systemic as well as supra-systemic estimated right ventricular systolic pressure. Conclusions: Left ventricular mass increases in infants supported with ECLS. These changes do not appear to be related to ventricular loading conditions. Further prospective work is needed to validate these findings and explore plausible mechanisms in this heterogenous group of patients.